2012
DOI: 10.3386/w18325
|View full text |Cite
|
Sign up to set email alerts
|

Hoping to Win, Expected to Lose: Theory and Lessons on Micro Enterprise Development

Abstract: Many basic economic theories with perfectly functioning markets do not predict the existence of the vast number of microenterprises readily observed across the world. We put forward a model that illuminates why financial and managerial capital constraints may impede experimentation, and thus limit learning about the profitability of alternative firm sizes. The model shows how lack of information about one's own type, but willingness to experiment to learn one's type, may lead to short-run negative expected ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Our point estimates suggest the combined effect is also greater than the sum of the individual treatment effects for a number of other outcomes, although large standard errors mean we cannot reject a lack of complementarity for most of these other outcomes. Existing work that combines treatments, such as Karlan and Udry (2012) who study the impact of cash transfers and business training for tailors in Ghana, or Gine and Mansuri (2011) who study loans and business training for Pakistani farmers, has not find any such evidence of complementarities. In both cases their power for detecting complementarities is relatively low, and they are looking for complementarities between business training and another business input, rather than for complementarities in who is trained.…”
Section: Government Of Indonesia and The World Bank And Implemented Imentioning
confidence: 99%
“…Our point estimates suggest the combined effect is also greater than the sum of the individual treatment effects for a number of other outcomes, although large standard errors mean we cannot reject a lack of complementarity for most of these other outcomes. Existing work that combines treatments, such as Karlan and Udry (2012) who study the impact of cash transfers and business training for tailors in Ghana, or Gine and Mansuri (2011) who study loans and business training for Pakistani farmers, has not find any such evidence of complementarities. In both cases their power for detecting complementarities is relatively low, and they are looking for complementarities between business training and another business input, rather than for complementarities in who is trained.…”
Section: Government Of Indonesia and The World Bank And Implemented Imentioning
confidence: 99%
“…benefit payments and a lump-sum benefit payment. A few recent experiments of the effects of business training on microentrepreneurs have been conducted in developing countries (Field, Jaychandran, and Pande 2010;Berge, Bjorvatn, and Tungooden 2011;Drexler, Fischer, and Schoar 2011;Karlan and Valdivia 2011;Karlan, Knight, and Udry 2012;Gine and Mansuri 2011). These studies have generally found some positive, but mixed, results.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxing these constraints encourages some entrepreneurs to experiment, but such experimentation will not necessarily lead to success and in fact on average will not succeed. Online Appendix A contains a model, originally developed in Karlan et al (2012), that formalizes this reasoning. Our results are consistent, therefore, with rational experimentation by entrepreneurs unsure about their ability to manage a larger, more sophisticated business.…”
mentioning
confidence: 99%